Late Holocene Fire and Climate History of the Western San Juan Mountains, Colorado: Results from Alluvial Stratigraphy and Tree-Ring Methods - Bigio, Erica Renee (The University of Arizona., 2013)
In the past few decades, wildfires have increased in size and severity in the Southwest and across the western US. These recent trends in fire behavior are a drastic change in arid, ponderosa pine and mixed conifer forests of the Southwest compared with tree-ring records of fire history for the past ~ 400 years. This study presents a late Holocene record (~ 3,000 years) of fire history and related changes in fire regimes with climate variability over annual to multi-decadal time scales. Tree-ring and alluvial-sediment sampling sites were paired in four small, tributary basins located in the western San Juan Mountains of Colorado. In our study sites, tree-ring records show that fire return intervals were longer and fire behavior was more severe on the north-facing slopes with relatively dense mixed conifer stands. Increased fire barriers and steep topography decreased the fire frequency and extent relative to gentle terrain elsewhere in the range and leading to a lack of synchrony among fire years in different parts of the study area. The alluvial-sediment record showed four peaks in high-severity fire activity over the past 3,000 years ranging between 200 - 400 years in length. The timing of peaks coincided with decadal-length drought episodes and were often preceded by multiple decades of above average winter precipitation. The sampling of alluvial-sediment and tree-ring data allowed for site-level comparisons between recent alluvial deposits and specific fire years interpreted from the tree-ring records. We found good correspondence between the type of fire-related sediment deposit (i.e. geomorphic response) in the alluvial record and the extent of mixed and high-severity fire estimated from the tree-ring record, and the correspondence was well-supported by the debris flow probability model results. The two paleofire data tend to represent particular components of the historical fire regime, with alluvial-sediments biased towards infrequent, high-severity events during recent millennia, and the tree-ring record biased toward lower severity fires during recent centuries. The combined analyses of different paleofire proxy types in the same study sites, therefore, can enhance and expand our understanding of fire and climate history beyond what is possible with either proxy alone.